The neuroprotective effects of Robusta coffee (Coffea canephora) on neurodegenerative diseases - Warman, Ressalia Shoumadani; Iqbal, Muhammad; Triyandi, Ramadhan (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2024)
Neurodegenerative diseases represent a growing global health challenge, particularly in aging populations. This review examines the neuroprotective potential of Robusta coffee (Coffea canephora) and its bioactive compounds in neurodegenerative conditions. Robusta coffee contains a rich profile of bioactive compounds, including caffeine, chlorogenic acids, and other polyphenols, which demonstrate significant antioxidant, anti-inflammatory, and neuroprotective properties. Evidence from preclinical and epidemiological studies suggests that these compounds can modulate multiple pathways involved in neurodegenerative processes, including oxidative stress, neuroinflammation, and protein aggregation. This review synthesizes current findings on the molecular mechanisms underlying the neuroprotective effects of Robusta coffee components in conditions such as Alzheimer's disease, Parkinson's disease, and other neurodegenerative disorders. Recent advances in delivery systems, such as nanoparticle formulations, are also discussed as potential approaches to enhance the bioavailability and efficacy of coffee bioactives. By identifying the therapeutic potential of Robusta coffee components and highlighting gaps in current knowledge, this review provides a foundation for developing novel preventive and therapeutic interventions for neurodegenerative diseases based on these naturally occurring compounds.